A modelling framework for MSP-oriented cumulative effects assessment. (August 2018) - Menegon, Stefano; Depellegrin, Daniel; Farella, Giulio; Gissi, Elena; Ghezzo, Michol; Sarretta, Alessandro; Venier, Chiara; Barbanti, Andrea
Graphical abstract: Highlights: A comprehensive Cumulative Effects Assessment (CEA) is presented. Sources of pressures are identified using a novel CEA backsourcing (CEA-B) model. A CEA impact chain visualization tool based on Sankey diagrams is proposed. Abrasion, marine litter and selective extraction are the most impacting pressures. CEA-B is an effective tool to address transboundary effects. Abstract: This research presents a comprehensive Cumulative Effects Assessment (CEA) based on the Tools4MSP modelling framework tested for the Italian Adriatic Sea. The CEA incorporates five methodological advancements: (1) linear and non-linear ecosystem response to anthropogenic pressures/effects, (2) modelling of additive, dominant and antagonist stressor effects, (3) implementation of a convolution distance model for stressor dispersion modelling, (4) application of a CEA backsourcing (CEA-B) model to identify and quantify sources of anthropogenic pressures affecting environmental components, based on the convolution distance model and (5) a novel CEA impact chain visualization tool based on Sankey diagrams. Results from CEA in the Italian Adriatic Sea show that highest CEA scores are located in the Northern Adriatic Sea (Port of Trieste and Venice Lagoon inlets) while abrasion, marine litter and selective extraction are the most pronounced pressures within the 12 nm. Results from CEA-B application for two case studies evidence a clear distinction among local human impacts (trawling, small scale fishery) versus long-range diffusive human impacts (underwater noise and marine litter). Results were discussed for their geospatial outcomes, importance for transboundary effects assessment, conservation planning and future application potentials.